(untitled) (Journal of Misan Researches, 2023)
The authority must adopt a specific policy with its nation, it bases on keeping their position stable, and reforming country rulers and judges are preoccupied with the lives of their religion and their worldly affairs from the affairs of the sultans and interfering in their affairs, so that goodness and prosperity prevail and everyone is happy. contrary the ruling authority is corrupted and its nation follow twisted methods and elect personalities who are obedient to it , are satisfied that they will be the tool for implementing its corrupt policy, then the prohibition will occur and the people will be corrupted, injustice and oppression will prevail in the country, so the voices of the revolutionaries against its policy and the men of its rule will rise. The Umayyad state produced; The state of tyranny and injustice, a group of men of power, took upon themselves the responsibility of ensuring the survival of its ephemeral authority During the humiliation of Muslims from the Arabs and the loyalists following various policies, at least of softness and severity, so they created defective miracles, so their criminal record filled the pages of history; Until their corruptions appeared that produced corrupted characters,families breeding service and obedience to their Umayyad masters, many of them began to race among them, competition and rivalry in the world of the Umayyads, tempted by the lust for power and driven by lust, so the struggle raged until reaching among them, and perhaps events developed into a declaration of disobedience. The Umayyad ruler deposed himself. Between Abd al-Rahman Ibn al-Ash’ath al-Kindi and al-Hajjaj al-Thaqafi, fierce wars occurred that harmed the country and the mankind.it represents explicit proof to the corruption of the Umayyad authority.